The Effect of Lean Management on Innovation Performance: How Absorptive Capacity Affects Food Manufacturing Industry? - Lithrone Laricha Salomon; Agustinus Purna Irawan; Eko Suhartanto (Advance Sustainable Science Engineering and Technology, 2026)
This study analyzes the effect of Lean Management Practices (LMP) on Innovation Performance (IP) through the mediating role of Absorptive Capacity (AC) in Indonesia’s food and beverage industry. A structured questionnaire adapted from validated instruments (Gaspersz, 2007; Cohen & Levinthal, 1990; Damanpour, 1991) was distributed to 200 managers and supervisors from food manufacturing firms listed in the Indonesian Ministry of Industry registry, yielding 180 valid responses (90% response rate). Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0, assessing reliability, convergent, and discriminant validity (HTMT ≤ 0.90). The results indicate that Lean Management strongly influences Absorptive Capacity (β = 0.919, p < 0.001) and both directly and indirectly enhances Innovation Performance (β = 0.690 and 0.725, respectively). Effect sizes (f² = 0.482 – 5.431) and R² > 0.83 confirm the model’s high explanatory power, while confidence intervals (95%) validate the path significance. These findings demonstrate that lean implementation enhances innovation effectiveness primarily through knowledge assimilation and transformation. The study’s main limitation is its single-sector, self-reported cross-sectional design, which may introduce common-method bias. Future research should apply multi-method or longitudinal approaches to increase generalizability.